An analysis of remanufacturing practices in Japan - Mitsutaka Matsumoto; Yasushi Umeda (Journal of Remanufacturing, 2011)
Purpose: This study presents case studies of selected remanufacturing operations in Japan. It investigates Japanese companies' motives and incentives for remanufacturing, clarifies the requirements and obstacles facing remanufacturers, itemizes what measures companies take to address them, and discusses the influence of Japanese laws related to remanufacturing. Methods: This study involves case studies of four product areas: photocopiers, single-use cameras, auto parts, and ink and toner cartridges for printers. Results and conclusions are based on the authors' discussions and interviews with 11 remanufacturers–four original equipment manufacturers (OEMs) and seven independent remanufacturers (IRs). In the discussions and the interviews, we asked the companies their motives for remanufacturing and asked the measures they take to overcome the obstacles of remanufacturing. This study highlighted three requirements for remanufacturing: (1) collection of used products, (2) efficient remanufacturing processes, and (3) demand for remanufactured products. Results: Where OEMs are the main remanufacturers of products covered by this study, their motives are long-term economic and environmental incentives. Where IRs are the main remanufacturers, it is often because OEMs shun remanufacturing, fearing to cannibalize new product sales. Companies' efforts to meet the above mentioned three requirements were observed and documented: (1) establishing a new collection channel; (2) developing reverse logistics to collect used products; (3) designing products for remanufacturing (DfReman); (4) accumulating know-how to establish remanufacturing processes; and (5) controlling product quality to stimulate demand for remanufactured products. This study also notes that (6) OEMs who engage in remanufacturing build consumer demand by incorporating remanufactured components into new products. This point has not been particularly noted in previous studies, but it has an important implication for OEMs' remanufacturing. The authors found that Japan's Home Appliances Recycling Law and End-of-Life Vehicle Law have promoted material recycling but have been insufficient to stimulate remanufacturing within the country. Conclusions: This study clarified the differences between OEMs' and IRs' remanufacturing. Both IRs and OEMs are important for remanufacturing. Institutional measures to encourage appropriate competition between OEMs and IRs and to enhance consumers' acceptance of remanufactured products is important to promote remanufacturing.
Keywords: 650; remanufacturing; practices in Japan; business obstacles; service; Automobilzulieferindustrie; Produkt-Recycling; Ersatzteil; Japan